Effects of gibberellic acid on growth and morphological variation of three kenaf (Hibiscus cannabinus L.) varieties - Tony Conrad, Priscilla (2018)
Kenaf (Hibiscus cannabinus L.), is one of the potential source to fulfil the demand of natural fibres for bio-composite and pulp and papers industry. However, due to the average fibre length of kenaf is below the critical length for bio-composite manufacturing, there is a need to improve its fibre’s length and quality. Kenaf plant elongation and improvement of fibre quality can be achieved by the use of plant growth regulators. Gibberellic acid (GA) is a plant hormone that can stimulate growth and development of plant. Therefore, this study is carried out to determine the effects of exogenous application of gibberellic acid on growth and morphological variations of three kenaf varieties which were V36, New Hybrid 2 and Fuhangyou No.2. These varieties were treated with two concentrations of gibberellins (0.0 and 2.0 mL/L). The effects of GA were observed for 16 weeks and the vegetative growth and morphological changes were assessed. The results found that gibberellic acid significantly increased the total height and basal diameter of kenaf, but failed to increase the leaf area and biomass in all kenaf varieties. GA also affected flowering behavior of kenaf varieties and seed production, where all the kenaf varieties treated with 2.0 mL/L concentration did not initiate any flowering. From this study, it can be concluded that GA provided significant effects on vegetative and reproductive growth of kenaf.